Computer-Mediated Communication and Family Communication among Deaf Teenager - Ramadhana, Maulana Rezi; Yusanto, Freddy (The Center for Disability Studies and Services Brawijaya University, 2020)
As a basis for parenting, communication can change patterns of interaction in the family. This study examines how computer-mediated communication (CMC) is related to and influences family communication (including conversation and conformity) in adolescents with disabilities. Participants in this study were 100 adolescents with deafness scattered in Indonesia. Through ANOVA analysis, the results show that CMC is significantly positively related to the conversation, conformity, and interaction between the two. Regression analysis found all four CMC factors as significant predictors affecting 50.4% in the climate of family communication among deaf teenagers. The findings in this study produce an empirical explanation of the CMC motive as a factor in family communication in deaf teens. Suggestions and research for the future are discussed.